Numerical Study on the Impact Instability Characteristics Induced by Mine Earthquake and the Support Scheme of Roadway - Guang-jian Liu; Shan-lin Li; Zong-long Mu; Wen Chen; Lei-bo Song; Jie Liu; Yu-dong Xu (Shock and Vibration)
Rockburst of deep roadway was induced by the superposition of mine earthquake disturbance and high static stress exceeding the limit strength of coal-rock mass. To study the roadway impact instability characteristics caused by mine earthquake disturbance and to propose an optimized support scheme, the discrete element model of the roadway structure was established based on the 1305 working face of the Zhaolou Coal Mine. The influence of mine earthquake amplitude and hypocenter location on the roadway was analyzed. The mesocrack evolution characteristics of the roadway were simulated and reproduced. Characteristics of stress field, crack field, displacement field, and energy field of the disturbed roadway with different support schemes were studied. The results showed that the greater the amplitude of the mine earthquake was, the severer the roadway impact failure was. The upper and left hypocenters had a significant influence on the roadway. The superposition of the high static stress and the dynamic stress due to the far-field mine earthquake resulted in the impact instability of coal-rock mass around the roadway, causing severe roof subsidence as well as rib and bottom heave. The evolution of tensile cracks caused the severe impact failure of roadway from a mesoscopic perspective. Using the flexible support to reinforce the roadway retarded the stress decline in roof and rib, improved the self-stability, reduced the number of near-field cracks, and decreased the displacement. Meanwhile, it allowed the roof and rib deformation, which was conducive to releasing elastic energy in surrounding rocks and reducing mine earthquake energy. The cracks and deformation in the floor were controlled by using the floor bolt. The optimal support scheme for a roadway to resist mine earthquake disturbance was proposed: “bolt-cable-mesh-steel strip-π-beam + floor bolt.” The research results have a specific guiding significance for the support of the coal mine roadway.